2019
DOI: 10.1002/mrm.28121
|View full text |Cite
|
Sign up to set email alerts
|

Chemical shift of 129Xe dissolved in red blood cells: Application to a rat model of bronchopulmonary dysplasia

Abstract: Purpose To measure the chemical shift of hyperpolarized 129Xe dissolved in the red blood cells(δRBC) of a cohort of rats exposed to hyperoxia and intermittent hypoxia (IH) to mimic human bronchopulmonary dysplasia, and to investigate the effect of xenon‐blood distribution time on δRBC. Methods δRBC was measured from spectra acquired using a chemical shift saturation recovery sequence from 15 Sprague‐Dawley rats exposed to hyperoxia‐IH and 10 age‐matched control rats. Sensitization to the xenon‐blood distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…3,9,[23][24][25][26][27][28][29][30] Both approaches have already been shown to be sensitive to various forms of lung disease. [31][32][33][34][35][36][37][38][39][40][41][42] More recently, efforts have been made to combine these methods by adding 2D or 3D spatial information to dynamic gas uptake measurements at the expense of lengthened scan times. 43,44 Nevertheless, although xenon uptake MR techniques for quantifying lung function have been in use for over 20 years, little attention has been paid to the impact of the acquisition parameters on the metrics extracted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,9,[23][24][25][26][27][28][29][30] Both approaches have already been shown to be sensitive to various forms of lung disease. [31][32][33][34][35][36][37][38][39][40][41][42] More recently, efforts have been made to combine these methods by adding 2D or 3D spatial information to dynamic gas uptake measurements at the expense of lengthened scan times. 43,44 Nevertheless, although xenon uptake MR techniques for quantifying lung function have been in use for over 20 years, little attention has been paid to the impact of the acquisition parameters on the metrics extracted.…”
Section: Introductionmentioning
confidence: 99%
“…The DP imaging techniques currently in use can be divided into two general types: (1) static measurements of the regional xenon distribution within the lung parenchyma as dictated by the structure and physiology of the lung, 9‐19 and the MR acquisition parameters, in particular the flip angle and the TR 20‐22 ; and (2) dynamic measurements that capture the xenon gas uptake by the lung tissue and transport by the pulmonary circulation as a function of time 3,9,23‐30 . Both approaches have already been shown to be sensitive to various forms of lung disease 31‐42 . More recently, efforts have been made to combine these methods by adding 2D or 3D spatial information to dynamic gas uptake measurements at the expense of lengthened scan times 43,44 .…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, our group reported lower δ RBC in rats exposed to hyperoxia/intermittent-hypoxia to model BPD in comparison to untreated control rats. 26 In that study, the exposed rats exhibited elevated oxygen desaturation following a hypoxic challenge as measured by pulse oximetry. Therefore, we surmised that the lower δ RBC observed in that study may be reflective of lower blood oxygenation during the anoxic breath holds used to administer 129 Xe.…”
Section: Discussionmentioning
confidence: 94%
“…Following previously described methods, 26 the RF pulses used for excitation and saturation were 90‐degree hard pulses (290 μs) calibrated using a series of constant flip angle excitation pulses applied to the in vivo gas signal. The center frequency of the RF pulses was then set to 197 ppm from the gas‐phase resonance (approximately at δ Plasma ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation